Assessing alternative assessment: students' experiences of the different forms of assessment in a Bachelor of Education course - Hendricks, Monica (Rhodes University, Faculty of Education, Department of Education, 2000)
In this study I examine the current alternative forms of assessment that were employed in the foundation year of the Bachelor of Education course at Rhodes University in 1998. Since assessment is concerned with ascertaining the amount, and kind, of learning that has taken place, it links learning and teaching. As my role in the course was academic development, I was interested in the nature ofthe development that the course promoted, for lecturers and students. My main intention was to gain insight into students' experiences of the assessment practices. To this end I selected six students, photocopied all their academic writing for the year and interviewed them. In addition, to provide a holistic picture of assessment and marking, I interviewed the six lecturers who team-taught the course. The data thus included the course assignments of the six students and an interview with each student as well as with the course lecturers. The findings show that though policy documents advocate alternative forms of assessment, implementing such assessment is a complex matter for both teachers and students.
Keywords: Education, Higher -- South Africa -- Evaluation; Educational tests and measurements -- South Africa